Design and Preliminary Validation of Social Assistive Humanoid Robot with Gesture Expression Features for Mental Health Treatment of Isolated Patients in Hospitals - Arce, D.; Gibaja, S.; Urbina, F.; Maura, C.; Huanca, D.; Paredes, R.; Cuellar, F.; Pérez-Zuñiga, G. (Springer Science and Business Media Deutschland GmbH, 2022)
Social and assistive robots have been widely discussed in the context of psychological interventions. These studies have confirmed that facial and body expressions increase perceived safety during human-robot interaction. In this paper, we present the design of a social assistive humanoid robot with articulated robotic arms intended to deliver telepsychological interventions. The design of the robot is presented, including the description of its features for interactive communication. The robot’s design and basic nonverbal communication were evaluated through an online behavioral experiment designed to examine the perceived valence and meaning of its gestures and the overall appraisal of its appearance. We found that the design of the telepresence robot was positively assessed by a sample (N = 34) of STEM-related participants according to Godspeed metrics. Moreover, we observed that the robot was able to perform gestures that were correctly identified and discerned in terms of their valence.
Keywords: Social assistive robot; Telepsychological interventions; Nonverbal communication; https://purl.org/pe-repo/ocde/ford#5.01.01